Biliary Lithiasis Basic Science, Current Diagnosis and Management - Borzellino, Giuseppe; Cordiano, Claudio; SpringerLink (Online service) (Milano : Springer Milan, 2008)
The book provides an overview on biliary lithiasis and all its clinical pictures, twenty years after the first laparoscopic cholecystectomy. The gallbladder, the main bile duct and intra-hepatic stones, in their uncomplicated and complicated forms are illustrated. Chapters are focused on basic science, epidemiology, diagnostic and therapeutic approaches to biliary lithiasis. The different diagnostic procedures described include invasive and noninvasive imaging, and treatment options take into consideration medical treatment, open and minimally invasive surgery, endoscopic and percutaneous approaches, both individually and as combined procedures. The book's content is not limited to the most commonly used therapeutic approaches reported in the literature, but also addresses new and innovative therapeutic strategies for biliary lithiasis. Thanks to its comprehensive approach, this volume will be of interest not only for GPs amd specialists in this field, but also to residents and other health professional of different disciplines.
Reflections on the Birth and on the Concept of Laparoscopic Surgery -- Epidemiology of Biliary Lithiasis -- Pathophysiology of Cholesterol Gallstone Disease -- Classification, Composition and Structure of Gallstones. Relevance of these Parameters for Clinical Presentation and Treatment -- Natural History of Biliary Lithiasis -- Preoperative Noninvasive Imaging -- Three-dimensional Imaging -- Endoscopic Retrograde Cholangiopancreatography and Endoscopic Ultrasound -- Pre- and Intra-operative Diagnostic Fibrocholangioscopy -- Intraoperative Cholangiography -- Laparoscopic Ultrasound during Laparoscopic Cholecystectomy -- Diagnostic Flow Charts for Biliary Lithiasis -- Medical Treatment of Gallstone Disease -- Surgical Treatment of Cholelithiasis: Exclusion Criteria -- Anesthesia in Biliary Lithiasis -- Cholecystectomy Techniques -- Robot-assisted Cholecystectomy -- Day Surgery Laparoscopic Cholecystectomy -- Diagnosis and Treatment of Acute Cholecystitis -- Incidental Carcinoma of the Gallbladder -- Complications of Laparoscopic Cholecystectomy -- Clinical Pictures of Common Bile Duct Stones -- Synchronous Treatment of Common Bile Duct Stones by Laparotomy -- Cholecystocholedocholithiasis: Two-stage Treatment -- Synchronous Treatment of Common Bile Duct Stones by Laparoscopy -- Rendez-vous Technique -- Flow Chart for the Treatment of CBDS and Critical Comparison of Techniques -- Common Bile Duct Stones in Cholecystectomized Patients -- Acute Biliary Pancreatitis -- Incidence and Management of Mirizzi Syndrome -- Biliary Lithiasis in Children -- Biliary Lithiasis in Pregnancy -- Biliary Lithiasis and Obesity -- Biliary Lithiasis in Patients with Gastroesophageal Reflux (Acid and Alkaline) -- Hepatic Cirrhosis and Biliary Stones -- Biliary Stones and Gastrectomy -- Biliary Ileus -- Clinical Pictures of Intrahepatic Lithiasis -- Treatment of Intrahepatic Lithiasis -- Extracorporeal Shock Wave Treatment of Gallbladder Stones -- Shock Wave for Main Bile Duct Stones -- Acute Gallstone Cholangitis: Clinical Pictures, Diagnosis and Treatment.
Keywords: Medicine; Radiology; Interventional radiology; Gastroenterology; Abdominal surgery; Minimally invasive surgery; Medicine & Public Health; Minimally Invasive Surgery; Abdominal Surgery; Interventional Radiology; Gastroenterology; Diagnostic Radiology; Electronic books